Reflections on Sam Harris' "Free Will" - Daniel C. Dennett (Rivista Internazionale di Filosofia e Psicologia, 2017)
In his book Free Will Sam Harris tries to persuade us to abandon the morally pernicious idea of free will. The following contribution articulates and defends a more sophisticated model of free will that is not only consistent with neuroscience and introspection but also grounds a variety of responsibility that justifies both praise and blame, reward and punishment. This begins with the long lasting parting of opinion between compatibilists (who argue that free will can live comfortably with determinism) and incompatibilists (who deny this). While Harris dismisses compatibilism as a form of theology, this article aims at showing that Harris has underestimated and misinterpreted compatibilism and at defending a more sophisticated version of compatibilism that is imprevious to Harris’ criticism.